Mycobacterium senegalense Tissue Infection in a Child After Fish Tank Exposure - Rachel Talavlikar; Julie Carson; Bonnie Meatherill; Shalini Desai; Meenu Sharma; Cary Shandro; Gregory J. Tyrrell; Susan Kuhn (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present report describes the first known case of an otherwise healthy child who developed a soft tissue infection due to Mycobacterium senegalense – a pathogen usually found in east Africa that is responsible for infecting various animals. The patient presented with nonhealing wounds after sustaining facial lacerations from the shattered glass of a fish tank. The patient responded well to scar revision and antibiotics, with no subsequent relapse.